Reinventing NASA : human space flight, bureaucracy, and politics - Handberg, Roger (Praeger, 2003)
From its beginnings, NASA was convinced that its real mission was to create the opportunity for a much different and better society on Earth, namely through human space flight. Pursuit of such a goal has led the agency to persist in certain activities even when they conflict with the wishes of Congress and the President. Recent changes in the international environment, changes that began well before September 11, 2001, have brought the military back into the field of human space flight, a situation that holds certain hazards for NASA since the military is more powerful politically. Dramatic changes could be in store, changes that could severely damage NASA's capacity for continuing what it sees as its primary objective.